Legible religion : books, gods, and rituals in Roman culture - MacRae, Duncan (Cambridge, Massachusetts : Harvard University Press, 2016)
"What was the significance of books in a religion without a sacred text? From the beginning of critical study of religion, the presence of Scripture - sacred and authoritative texts - has divided a few privileged Religions of the Book from other religions, including Roman religion, that lack such books. Arguing that we should look beyond this distinction, Legible Religion examines the role of books in Roman religious culture. In order to get at the question of the place of books in religion, the study includes an extended comparison between Roman books on their religion and the Mishnah, an early Rabbinic compilation of Jewish practice and law, to highlight how non-Scriptural texts can play an important part in the demarcation of religious systems."--Provided by publisher.
Introduction: The books of Numa -- Part I: Writing Roman religion -- Gods and humans in Rome and its empire -- Writing Roman religion -- Letters of the republic -- Part II: Comparison -- Rabbis and Romans -- Part III: Reading Roman religion -- Emperor as reader -- Paper pagans -- Conclusion: Beyond scripture and literature.
Includes bibliographical references and index.
Print version record.
In English.
Master record variable field(s) change: 072
Keywords: Mishnah -- Comparative studies; Mishnah; Rome -- Religion; Sacred books; Gods, Roman, in literature; Religion and literature -- Rome; BODY, MIND & SPIRIT -- Spirituality -- Paganism & Neo-Paganism.; RELIGION -- Antiquities & Archaeology; Gods, Roman, in literature; Religion; Religion and literature; Sacred books; Rome (Empire); RELIGION / History; Electronic books; Comparative studies